Hydrogen Sulfide: A Worthwhile Tool in the Design of New Multitarget Drugs - Sestito, Simona; Nesi, Giulia; Pi, Rongbiao; Macchia, Marco; Rapposelli, Simona (Frontiers in Chemistry, 2017)
H2S is a gaseous molecule able to trigger a plethora of central physiological and pharmacological effects as antioxidant, pro- and anti-inflammatory, pro- and anti-nociceptive, neuromodulator, and cytoprotective. The polypharmacology of H2S depends on the wide variety of targets implicated, but, despite the efforts, the mechanisms of action that should clarify its activity are still not completely unrevealed. Nevertheless, many attempts to exploit the multifaceted profile of this molecule have already been accomplished and many chemical entities containing an H2S-releasing pharmacophore have been synthetized. Here we discuss recent investigations on multitarget molecules able to release H2S, with a particular focus on the combinations of “native drug” with moieties structurally able to release H2S and their applications as therapeutic tools in bone disease, gastrointestinal system and neurodegenerative disorders.